Clima urbano em cidades pequenas e médias: uma breve revisão - Oliveira, Jefferson de Jesus (Universidade Federal de São Carlos, 2023)
Understanding how the expansion of urban areas has affected temperatures in cities is a daunting task for scholars in the field. Many studies have focused on understanding the impacts on large urban centers, but in Brazil, small and medium-sized cities have been the subject of more recent studies. The urban heat island is a consequence of anthropogenic processes on the urban surface, which can be exacerbated by the lack of planning and management that considers environmental aspects and environmental quality in urban areas. This study is the result of an analysis of research related to urban climate and the heat island, conducted through a brief review. Two keywords were used: "Heat island" and "Urban climate" within the Google Scholar research platform, covering the period from 2000 to 2019. Only geographical studies on small and medium-sized cities conducted in institutions throughout Brazil were selected for analysis. Therefore, the aim of this work is to shed light on, systematize, and analyze Brazilian scientific production on the topic of Urban Climate and Heat Island, through articles, dissertations, and theses. It was possible to identify 90 studies carried out in 106 cities, which are distributed as follows: 61 articles, 6 undergraduate theses, 14 master's theses, and 9 doctoral theses. It is considered that the number of studies presented is small, considering a 20-year time frame and the territorial dimension of Brazil. However, in recent years, there has been a significant increase in this thematic area in the field of geography. It can be asserted that climate studies have sought to understand the effects of urbanization on small and medium-sized cities and contribute to policies for improving urban environmental quality.
Urban climate on small and medium sized cities: a brief revision
Keywords: Ilha de Calor; Clima Urbano; Cidades Pequenas e Médias; Google Acadêmico; Heat Island; Urban Climate; Small and Medium Cities; Google Scholar; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::CLIMATOLOGIA GEOGRAFICA